Effects of Short- and Long-Term Soy Protein Feeding on Hepatic Cytochrome P450 Expression in Obese Nonalcoholic Fatty Liver Disease Rat Model - Kozaczek, Melisa; Bottje, Walter; Albataineh, Diyana; Hakkak, Reza (Frontiers in Nutrition, 2021)
Obesity can lead to chronic health complications such as nonalcoholic fatty liver disease (NAFLD). NAFLD is characterized by lipid aggregation in hepatocytes and inflammation of the liver tissue as a consequence that can contribute to the development of cirrhosis and hepatocellular carcinoma (HCC). Previously, we reported that feeding obese Zucker rats with soy protein isolate (SPI) can reduce liver steatosis comparing to a casein (CAS) diet as control. However, the effects of SPI on cytochrome P450 (CYP) in an obese rat model are less known. In addition, there is a lack of information concerning consumption of soy protein in adolescents and its effect in reducing early onset of NAFLD in this group. Our main goal was to understand if SPI diet had any impact in hepatic CYP gene expression comparing to CAS diet. For this purpose, we used transcriptomic data obtained in a previous study in which liver samples were collected from obese rats after short- (8 weeks) and long-term (16 weeks) feeding of SPI (n=8 per group). To analyze this RNAseq data, we used Ingenuity Pathway Analysis (IPA) software. Comparing short- vs long-term feeding revealed an increase in the number of down-regulated CYP genes from three at 8 weeks of SPI diet to five at 16 weeks of same diet (P ≤ 0.05). On the other hand, upregulated CYP gene numbers showed a small increase in long-term SPI diet compared to short-term, from 14 genes at 8 weeks to 17 genes at 16 weeks (P ≤ 0.05). The observed changes may have an important role in attenuation of liver steatosis.